2022
DOI: 10.3389/fsufs.2022.724321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 Pandemic on Food Systems and Determinants of Resilience in Indigenous Communities of Jharkhand State, India: A Serial Cross-Sectional Study

Abstract: The COVID-19 pandemic has globally jeopardized food security, with heightened threats for the most vulnerable including smallholder farmers as well as rural, indigenous populations. A serial cross-sectional study was conducted to document effect of COVID-19 pandemic on food environment, agricultural practices, diets and food security, along with potential determinants of food systems resilience, among vulnerable smallholder farmer households in indigenous communities of Santhal, Munda, and Sauria Paharia of Jh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 48 publications
3
20
0
1
Order By: Relevance
“…Similar observations have been made in other Indigenous contexts (Finnis, 2007;Sheehy et al, 2013). More importantly, reliance on purchased food items might increase food access vulnerability to livelihood disruptions and/or price increases, as for example evidenced during the COVID-19 pandemic (Stanger-McLaughlin et al, 2022;Ghosh-Jerath et al, 2022).…”
Section: Associating Observed Diet Change In Gunalaya With Trends In ...supporting
confidence: 54%
“…Similar observations have been made in other Indigenous contexts (Finnis, 2007;Sheehy et al, 2013). More importantly, reliance on purchased food items might increase food access vulnerability to livelihood disruptions and/or price increases, as for example evidenced during the COVID-19 pandemic (Stanger-McLaughlin et al, 2022;Ghosh-Jerath et al, 2022).…”
Section: Associating Observed Diet Change In Gunalaya With Trends In ...supporting
confidence: 54%
“…On the contrary, some food groups, such as dark leafy greens depended on a shorter, more local, supply chain and were reported to be easier to acquire and had a higher reported consumption particularly in the rural communities. Similar studies, which used a variation of the C-SCAN survey, found that households in China and India that relied primarily on cultivated food environments, and, therefore, shorter more local supply chains, were more resilient to negative changes in the food system and had to change their diet less to accommodate for those negative changes [ 12 , 22 ]. In addition to an impact diet quality, the COVID-19 pandemic had a large impact on food security.…”
Section: Discussionmentioning
confidence: 99%
“…These areas were selected based on prior work conducted by members of the study team [ 17 , 18 , 19 , 20 , 21 ]. The total sample size ( n = 300) was selected based on sample size calculations conducted by similar researchers using the same rapid assessment (C-SCAN) in other geographical locations [ 12 , 22 ]. In order to reach the total sample size in both settings, a larger study sample was approached for participation in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Covid-19 pandemic had significantly disrupted national health programs in India including the ICDS due to lockdowns, fear of infection in the public, and diversion of frontline workers for other Covid-related duties which potentially compromised the sustainability of existing food systems, especially amongst vulnerable communities [ 14 ]. However, there is a paucity of information on the utilization of ICDS in Northern India during the period of the Covid-19 (THR) pandemic.…”
Section: Introductionmentioning
confidence: 99%